Making Liquid Sugar Preparations from Lombok-Traditional Sugarcane Juice and Its Potential as Anti-Diabetic Sugar - Nurul Furqan, Baiq Repika; Maharani, B Fitria (Universitas Islam Negeri Mataram, 2022)
The prevalence of Patients with Diabetes Mellitus remains on the rise worldwide. Diabetes is a multifactorial disorder that emboils genetic and environmental factors such as an unhealthy diet by consuming white sugar crystals. White crystal sugar consists of less chromium content that induces glucose in the blood to the cells, which can trigger hyperglycemia or high blood sugar levels. Chromium works by increasing the activity of insulin receptors to enhance glucose translocation to the cell. Previous studies showed sugarcane Nira had a high level of chromium compared with those processed into white crystalline sugar. However, it could not be used as a sweetener substitute since its storage age was only 2 to 3 days. This study identified that the treatment process of Lombok's Nira sugarcane into local liquefied sugar should be addressed to maintain chromium levels compared to the processing of Nira into the white crystalline sugar requiring optimum sucrose and omitting several minerals. Hence, sugarcane Nira as a refined sugar product can substitute for white sugar consumption in diabetes patients.